2018
DOI: 10.1097/sap.0000000000001500
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Factors Associated With Comorbidities for Treatment Response in Outpatients With King Classification III Diabetes Foot Ulcers

Abstract: Previous PTA and retinopathy, which indicated preexisting severe vasculopathy, are univariate predictive factors for treatment failure and nonsuccess, respectively, in patients with King classification III DFU. With the subdivision of King classification III DFU, medical history taking and fundus examination are acceptable methods for risk screening at an outpatient clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, this was only shown in univariable analysis. 30 Our study suggests that the chance to heal a wound is depended on whether the wound is deep or superficial. In our study, we have shown that a deeper wound, known as UT classification grade 2 and UT classification grade 3, is related to hard-to-heal wounds and that time to healing is negatively influenced by these two predictors.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, this was only shown in univariable analysis. 30 Our study suggests that the chance to heal a wound is depended on whether the wound is deep or superficial. In our study, we have shown that a deeper wound, known as UT classification grade 2 and UT classification grade 3, is related to hard-to-heal wounds and that time to healing is negatively influenced by these two predictors.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study also suggested a predictive role for previous percutaneous transluminal angioplasty or retinopathy for treatment failure in patients with a DFU. However, this was only shown in univariable analysis …”
Section: Discussionmentioning
confidence: 92%